Pentingnya Mentor Sebagai Pemimpin Penggembala Pada Kelompok Guru [The Importance of a Mentor as a Shepherd Leader in a Group of Teachers] - Rumanti, Elisabet Dewi (Jurnal Teropong Pendidikan, 2024)
XYZ School is a Christian school in Manado that has implemented teacher mentoring program since the school was established. Changes in the implementation of mentoring programs that were designed in structured way created anxiety for leaders who had to become mentors about their leadership ability to focus not only on professional development, but also on shepherding role. This research aims to determine how deep the role of mentor as shepherd leader is in professional development, identify challenges faced by mentor and how to overcome it, and identify the impact of mentor’s role as shepherd leader on the process of forming mentee’s life formation. This study uses qualitative approach with an exploratory case study design. Determination of informants is done by purposive and snowball sampling as many as fourteen informants. The research showed that mentors are a shepherding leader in professional development through various intentional activities in mentoring meetings. Mentor struggles with challenges from within. In facing challenges, mentor experiences life changes and growth, then processed in response to God's calling. The small group context builds deep relationships that helps mentor to know, feed, lead, and to be a role model. Mentor’s life changes and deep relationships have influenced mentee and inspired process of forming their life formation